2014
DOI: 10.1007/s11356-014-3873-9
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of benthic diatom adhesion and photosynthetic activity by allelopathic compounds from a green alga: involvement of free fatty acids?

Abstract: The role of chemical interactions in shaping microbial communities has raised increasing interest over the last decade. Many benthic microorganisms are known to develop chemical strategies to overcome competitors, but the real importance of chemical interactions within freshwater biofilm remains unknown. This study focused on the biological and chemical mechanisms of an interaction involving two benthic microorganisms, an allelopathic filamentous green alga, Uronema confervicolum, and a common diatom, Fistulif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…For example, synthesis of allelopathic substances, e.g., antibiotics and other inhibitors, by members of the biofilm community plays an essential role in determining microbial diversity and structure (Lenski and Riley, 2002;Burmolle et al, 2006). Studies on biofilms of different origin and bacterial associations with eukaryotic hosts, e.g., human pathogens (Harriott and Noverr, 2009;Lopes et al, 2012;Korgaonkar et al, 2013), as well as aquatic microbial and epiphytic communities (Burmolle et al, 2006;Allen et al, 2015;Kouzuma and Watanabe, 2015;Dittami et al, 2016), have revealed both synergistic and antagonistic inter-species interactions. It is well-known that bacteria are able to stimulate growth, morphogenesis, and zoosporogenesis of algae (Marshall et al, 2006;Goecke et al, 2013) as well as the synthesis of algal extracellular compounds (Bruckner et al, 2011).…”
Section: Interactions Between Auto-and Heterotrophs In Aquatic Microbmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, synthesis of allelopathic substances, e.g., antibiotics and other inhibitors, by members of the biofilm community plays an essential role in determining microbial diversity and structure (Lenski and Riley, 2002;Burmolle et al, 2006). Studies on biofilms of different origin and bacterial associations with eukaryotic hosts, e.g., human pathogens (Harriott and Noverr, 2009;Lopes et al, 2012;Korgaonkar et al, 2013), as well as aquatic microbial and epiphytic communities (Burmolle et al, 2006;Allen et al, 2015;Kouzuma and Watanabe, 2015;Dittami et al, 2016), have revealed both synergistic and antagonistic inter-species interactions. It is well-known that bacteria are able to stimulate growth, morphogenesis, and zoosporogenesis of algae (Marshall et al, 2006;Goecke et al, 2013) as well as the synthesis of algal extracellular compounds (Bruckner et al, 2011).…”
Section: Interactions Between Auto-and Heterotrophs In Aquatic Microbmentioning
confidence: 99%
“…For example, studies on cell cultures of the brown alga Ectocarpus had shown that presence of specific associated bacteria increase the tolerance of the algal host to low salinity (Dittami et al, 2016). Besides synergistic interactions, a multispecies community inevitably faces competitive antagonistic interactions among species (Freilich et al, 2011;Allen et al, 2015;Yuan and Meng, 2020). Last, studies have shown that in the absence of carbon limitation, heterotrophs can out-compete algae for nutrients and thus suppress algal growth (Wyatt et al, 2019).…”
Section: Interactions Between Auto-and Heterotrophs In Aquatic Microbmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies have demonstrated that filamentous green algae (FGA) use chemicals to ensure their dominance (Leflaive et al, 2008b;Trochine et al, 2011). Biofilm forming green algal allelochemicals have rarely been identified, but it has been shown that one species, Uronema confervicolum, probably produces an array of different allelopathic compounds (Allen et al, 2015).…”
Section: High Diversity Of Reported Allelopathic Interactionsmentioning
confidence: 99%